Microencapsulation in Food Science and Biotechnology in Iraq - Marwah Ali Oudah (Journal of Global Pharma Technology, 2020)
microcapsules can release their contents at controlled speeds under specific conditions, and can protect the encapsulated product from light and oxygen. The microencapsulation consists of microparticles formed by a porous polymeric membrane containing an active substance. The material or mixtures of materials to be encapsulated can be covered or trapped within another material or system. A microcapsule consists of a semi-permeable, spherical, thin and strong membrane around a solid / liquid center. The materials used for encapsulation can be gelatin, fats, oils, gum arabic, calcium alginate, waxes, wheat starch, corn, rice, potatoes, nylon, cyclodextrin, maltodextrin, sodium caseinate, whey protein or protein of soy. The applications of microencapsulation are directed to the industry, it is given to the textile, metallurgical, chemical, food, cosmetics, pharmaceutical and medical industries. Among the techniques used to microencapsulate are spray drying, cooling drying, freeze drying, coacervation and extrusion. The substances that are microencapsulated can be vitamins, minerals, dyes, prebiotics, probiotics, nutraceutical flavors, antioxidants, odors, oils, enzymes, bacteria, perfumes, drugs and even fertilizers.Keywords: Encapsulation techniques in food, Encapsulation theory.